ANALISIS JARINGAN BASE TRANSCEIVER STATION (BTS) SIDOMULYO TERHADAP PERFORMANSI JARINGAN PT. INDOSAT SINTANG - Tri Widia Ningsih . (Faculty of Engineering, Universitas Tanjungpura, 2015)
The world of communication and information technology in Indonesia have been the basic needs for everyone. The growth of GSM technology is expected to accomodate data and voice services. Therefore, it is needed a well preparation for applying GSM network and for optimizing the network in order to achieve an optimal and profitable network. In this research, the reseracher conducted a measurement on network performance to see the difference on site BTS Sidomulyo performance to its hardware charging such as power system, transmission, and antenna. In order to find the problem exists, it is needed the supporting data such as cluster and Call statistic, by using those data it will be known the difference of using the old hardware and new hardware. Those data are the parameters of the connection endurance level which is occured among voice service networks. Drive test is needed to collect the data from the result of signal quality measurement on a network. The writer used the data from a vendor called PT. Indosat and from those data taken on October 7th 2014. The analysis on GSM network performance which is analyzed based on KPI parameter called call statistic is gained by using G-NetTrack, while CSSR, CDR and CSR are gained by using formula. CSSR gained 96,67%, CDR gained 3,33%, gained 93,38% which show that the network performance is good. Based on the use of BBM in one month is, genset usage costs Rp. 23.236.000,00 while PLN usage costs Rp. 5.210.000,00 from the calculation of those sources it is concluded that PLN usage is more economical rather than genset usage with the different about Rp. 18.025.500,00. Keywords : Network performance, Key Performance Indicator, drive test